Refocusing, Reimaging, dan Rebuilding Sekolah Muhammadiyah - Kholid, Muhammad Noor; Faiziyah, Nuqthy; Sutama, Sutama; Hidayati, Yulia Maftuhah; Sayekti, Ika Candra; Pramudita, Dias Aziz (Jurnal SOLMA, 2024)
The service partner is MI Muhammadiyah Sidoharjo (MIM Plasan). The condition of school among: student achievement in academic and non-academic activities still needs to be optimized, teachers have pedagogic competencies that still need to be improved, teachers' abilities in mastering technology to support learning need to be developed, do not yet have a school website, and communication networks and partnerships need to be strengthened. The purpose of this service is to rebuild the image of MIM Plasan so as to gain public trust. The methods carried out are champion school workshops, learning development workshops, IT integration workshops in learning, school web and social media development, and strengthening cooperation networks. The results obtained are: the formation of teams and strategies for champion schools, the development of more comprehensive teacher competencies in compiling kit and integrating them with IT, as well as social media and websites that are more updated regularly. The school feels a direct impact in service activities.